Three‐Component Domino Knoevenagel/Vinylogous Michael Reaction: Entry to Challenging o‐Terphenyls. Issue 25 (8th March 2018) - Grau, Dominik; Grau, Benedikt W.; Hampel, Frank; Tsogoeva, Svetlana B.
Abstract: An unprecedented organocatalytic three‐component domino Knoevenagel/vinylogous Michael reaction starting from simple enolizable aldehydes, malononitrile, and nitroolefins is reported. This facile two‐step domino process provides a straightforward stereoselective route to multifunctional vinyl malononitrile products (up to 82 % yield, 85:15 d.r.) containing a nitroalkane moiety, and contributes to the development of sustainability and atom economy. The application of the obtained domino products for synthesis of highly functionalized o ‐terphenyls (of high interest for materials science and medicinal chemistry) through subsequent new three‐step domino reaction involving cyclization–tautomerization–aromatization steps, has been demonstrated. Abstract : All‐in‐one synthesis : An unprecedented three‐component domino Knoevenagel/vinylogous Michael reaction, providing a straightforward diastereoselective route to multifunctional vinyl malononitrile products is presented (see scheme). The applications of the new domino products for facile synthesis of highly functionalized o ‐terphenyls through a subsequent new three‐step linear domino process, has been demonstrated.